USING ENGLISH VIDEO CONVERSATION â€œASKING AND GIVING OPINIONâ€ TO IMPROVE STUDENTSâ€™ SPEAKING ABILITY - Ningsih, Fatma; Ikhsanudin, Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed at improving the eighth- grade students of SMP N 2 Pontianak speaking ability in Academic Year 2017/2018. This research used English video conversation